Removal of arsenic from drinking water by precipitation and adsorption or cementation: An environmental prospective - Tiwari, S K; Pandey, V K (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">The removal of arsenic from process solutions and effluents has been practiced by the mineral process industries for many years. More recently, because of the recognition that arsenic at low concentrations in drinking water causes severe health effects, the technologies that have been used in the mineral industry are being applied to that situation. Removal of arsenic in process solutions can be accomplished for most present day product specifications but the stability of solid and liquid waste materials for long-term disposal or discharge may not meet the regulatory requirements of the future. In the case of drinking water treatment where the requirement is to reduce arsenic to a few parts per billion, the applicable technologies are limited. This paper mentions briefly the aqueous inorganic chemistry of arsenic and the most common methods that have been applied commercially in the mineral industry for arsenic removal, recovery, and disposal. Some techniques, which have been used only in the laboratory, or otherwise suggested as means of eliminating or recovering arsenic from solution, are also outlined. Low cost removal of arsenic from drinking water is likely to be confined to precipitation, adsorption or cementation, but the sludge’s created present stability concerns. This paper reviews some of the work done in relation to the mineral industry where there is also application to drinking water. Disposal of stable residues is critical in both situations, and the testing methods for assessing stability need careful consideration.